Implication of Salivary Chemerin in Diagnosis of Oral Squamous Cell Carcinoma - A Review - Sidrah Mahmood Mughal; Sana Mirza; Mervyn Hosein; Moazzam Ali Shahid (ziauddin University, 2024)
The development of salivary biomarkers of oral squamous cell carcinoma (OSCC) is the area of great interest and research. OSCC is ranked as, the sixth most common cancer worldwide. Most often, its symptoms are not evident during the initial stages or even absent until the cancer has metastasized. If detected early, the rate of cure may be as high as 50%. Hence, there is a dire need to develop diagnostic tools, which may help in early detection and differentiation between high-risk individuals, oral pre-malignant lesions and OSCC. Recently, increased levels of salivary biomarker Chemerin have been shown to be associated with malignant tumors. Since, the validity of any biomarker is the most challenging task for the researcher therefore, there is still debate going about its circulating effects on OSCC growth, whether high levels of Chemerin may act as a valuable biomarker for OSCC. The information was extracted from search engines including Medline, Google Scholar and PubMed through different research papers from 2000-2020. The review emphasized the need to conduct further studies on the significance of Chemerin. Very few studies have shared the association between Chemerin and detection of oral cancer. However, this relationship is strong enough to claim Chemerin as an important diagnostic marker during diagnosis of oral cancer. Keywords: Chemerin; Oral Squamous Cell Carcinoma; Biomarker; Neoplasm Metastasis; Proteins.